Playing the game: a realist approach to evaluating online student access, retention, progression and attainment initiatives - Clark , Daniel (Research in Learning Technology, 2022)
This study presents an evaluation of an online game-based student access, retention, progression and attainment (ARPA) initiative at the University of Kent. The initiative, a narrative-based simulation of a condensed student journey from pre-enrolment to graduation, is designed to prepare and support students in their transition to and participation in Higher Education. Student retention continues to be a perennial issue across the Higher Education sector, and studies have indicated that the more knowledgeable and informed students are about their university environment, the less likely they are to leave before completing their studies. Many institutions have developed interventions with the express purpose of addressing these concerns. Recognising the contextualised and subjective nature of such interventions, a realist evaluative framework was adopted to better understand the initiative under scrutiny, asking what works, for whom and in what circumstances. Participant interviews were utilised to assess the efficacy of the initiative in supporting students and in helping them to navigate often unfamiliar institutional cultures, practices and expectations. A revised programme theory is presented, enabling deeper insight into the merit of the initiative and its overall worth as a mechanism for change within the ARPA paradigm.